BASIC EDUCATION: THE IMPORTANCE OF PARENT PARTICIPATION IN THE EDUCATIONAL PROCESS OF THEIR CHILDREN AND THEIR RELEVANCE: BASIC EDUCATION: THE IMPORTANCE OF PARENT PARTICIPATION IN THE EDUCATIONAL PROCESS OF THEIR CHILDREN AND THEIR RELEVANCE - Silva, Edinete Nunes da; Alencar, Evilazio Nascimento; Alves, Francisco Eduardo Ferreira; Braga, Yanne Mayara Leite; Querino, Luana Lindolfo; Batista, Luzia Gleiciiana; Silva, Robelha Caetano da; Nascimento, Sebastião Pedro do; Souza, Viviane Dantas de; Feitosa, Ankilma do Nascimento Andrade (Brazilian Journal of Production Engineering, 2020)
This work sought to verify the importance of parents’ participation in their children’s educational process. It is an integrative literature review, which was based on the following guiding question: What is the relevance of parental participation during their children’s educational process? Then, a search for articles was carried out in the SCIELO database, where 43 articles were found, using the keywords: Basic Education, School and Family. In the search, the Boolean operator AND was used. The following inclusion criteria were used: articles published in the last 5 years, made available in full, published in Portuguese and Spanish and that reached the proposed objective, after full reading. Articles that dealt only with health education and those that did not portray the figure of parents as agents of early childhood education were excluded. At the end, 3 articles were selected to compose the study. The search for articles took place between July and August 2020. Family participation during the children’s education process arouses interest and motivation, encouraging them to study, as well as having a continuity of the learning process outside of school. In view of this, the family and the school must have a direct relationship with the learning process, as these form an important binomial in the growth of the human person as a citizen with a cognitive, critical and social sense. In view of this, parental participation in the educational context is indispensable for child development, since education is carried out through the school-family-society triad.